Conductance investigation of p‐MIECs fabricated by poly(3, 4‐ethylenedioxy thiophene), polyacrylic acid, polyethylene oxide, and lithium‐ion salt. Issue 11 (1st July 2014) - Xu, Huihui; Cui, Jidi; Pan, Chunyue; Yu, Guipeng; Hong, Shiyu; Wang, Xipeng; Yao, Zhijiang
<x xml:space="preserve">Abstract</x> Polymer blends and composite films were facilely prepared from their aqueous solutions with varying contents of poly(3, 4‐ethylenedioxythiophene) (PEDOT), polyethylene oxide (PEO), and polyacrylic acid (PAA). The physicochemical and electric properties of the composite films were analyzed by Raman spectra, infrared spectra (FT‐IR), scanning electronic microscopy (SEM), thermogravimetric analysis (TGA), and four‐point probe method. PEDOT was successfully incorporated into each blend which was confirmed by spectra analysis. The crystallization of PAA or PEO and the structure of PEDOT should be taken into consideration for the electronic conductivity. According to Raman spectra, in the case of PEDOT–PAA–PEO, conformation of the PEDOT backbone changed from the quinoid to the benzoid structure partly. The ionic conductivities of lithium‐ion salt‐mixed PAA–PEO and ternary blend were characterized by AC impedance spectroscopy. The ternary blend with LiCoO2 presents good electronic and ionic conductivity, and it appears to be a new candidate for polymeric mixed ionic electronic conductor. POLYM. COMPOS., 36:2076–2083, 2015. © 2014 Society of Plastics Engineer